Investigation of Borrelia burgdorferi antibodies in patients with multiple sclerosis - Ildız, Nilay; Özerol, İbrahim Halil and Özcan, A. Cemal and Çelik, Hamit (Asian Journal of Medical Sciences, 2020)
Background: Lyme is a disease that is non-compulsory in our country and whose seroprevalence data is less studied. Aims and Objective: Recent studies have shown that bacterial and viral infections are risk factor for various neurodegenerative diseases such as multiple sclerosis and Alzheimer’s disease. Herein, we aim to determine the seroprevalence of Lyme in multiple sclerosis (MS) patients. For this purpose, 100 MS patient’s serums were investigated for Borrelia burgdorferi IgM and IgG positivity. Materials and Methods: The results identified with ELISA as positive antibody was confirmed by Western Blot (WB) test. The correlation between ages, gender, occupation, tick history, existence of erythema chronicum migrans (ECM), antibody positivity, pain, year with MS results were investigated using Kolmogorov-Smirnow and Kruskal-Wallis statistical test. Results: B. burgdorferi IgM and IgG antibodies were positive in 8% patients when using ELISA method, but that were found to be 2% by WB. ELISA IgM antibody test gave a 5 negative result in WB. These results were considered false positive in the ELISA test. So, altogether 5 patients were positive by WB method. None of syphilis positive samples detected that B. burgdorferi positive serum. A significant difference between the parameters in terms of IgM positivity was not detected (p> 0.05). B. burgdorferi IgG antibodies were found significant differences between the MS disease duration (p = 0.03). MS in the group of less than 10 years had higher titers of IgG antibodies to B. burgdorferi. Conclusion: Although a small number of patients with MS is positive with Lyme antibodies. Lyme disease is a treatable.Also, If the patient is MS, clinician should be considered Lyme in the differential diagnosis. This is the first study that the correlation between Lyme and MS from Turkey.